12-m-9m=-20-12m

Simple and best practice solution for 12-m-9m=-20-12m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12-m-9m=-20-12m equation:


Simplifying
12 + -1m + -9m = -20 + -12m

Combine like terms: -1m + -9m = -10m
12 + -10m = -20 + -12m

Solving
12 + -10m = -20 + -12m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '12m' to each side of the equation.
12 + -10m + 12m = -20 + -12m + 12m

Combine like terms: -10m + 12m = 2m
12 + 2m = -20 + -12m + 12m

Combine like terms: -12m + 12m = 0
12 + 2m = -20 + 0
12 + 2m = -20

Add '-12' to each side of the equation.
12 + -12 + 2m = -20 + -12

Combine like terms: 12 + -12 = 0
0 + 2m = -20 + -12
2m = -20 + -12

Combine like terms: -20 + -12 = -32
2m = -32

Divide each side by '2'.
m = -16

Simplifying
m = -16

See similar equations:

| x+8=1-6x | | -4w-5(-7x+4w)+6x= | | -3(x-5)-(2x+13)=-4(2x+2)+2(x-3)-2x-4x | | x+10=-y+10 | | -4(-3w-3z)-2(-6z-w)= | | 5x-2-3x=17+12x-23 | | 8f+9=21 | | 5n-n=0 | | -2(3h-1)=5(2h-3) | | g+9+7g=-11+9g | | 2a+4=5a-8 | | 26+8m=6-4(1-5m) | | 9-10v=-9v+13 | | 5(y+5)=y+37 | | -3[x+6]+5=-4 | | 4(5-w)=2(2w-3) | | 36=0.9y | | 0.04a+0.02(a-4)=0.3(0.1a-0.2) | | 13t+(-12)=12t+(-12t)+3.14 | | -5[x+6]+5=-10 | | y=-1.3(10+87.5) | | 300x^2-1200=0 | | k=ax+b | | -9-9h+h=9-6h | | -6x+7x=3 | | 2[x+8]=-6x-14 | | 3.1=4.9-0.9x | | 5=m-5(4) | | 12t-22=5t-1 | | (4u+2)(9+u)=0 | | (1/3)(x+4)=2x-3 | | -10+d=9-6d+9 |

Equations solver categories